Bioprocessing of organic wastes from poultry and bovine slaughterhouses as food substrate for Hermetia illucens larval development - A.P. Luperdi; S.S. Flores-Calla; X.J. Barriga; V. Rivera; I. Salazar; P.L. Manrique; J.E. Reátegui (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: In the meat industry, inefficient management of organic waste exists, therefore the study aims to evaluate different bovine and poultry organic residues as food substrates during larval development of the black soldier fly, such as a sustainable alternative to obtain high protein meal.METHODS: The research evaluates the use of organic waste from cattle and poultry slaughterhouses, as food substrate for black soldier fly larvae, including raw beef blood T1, raw beef viscera T2, cooked beef blood T3, cooked beef viscera T4, raw chicken viscera T6 and cooked chicken viscera T7; further, as a control measure balanced feed (7 treatments and 5 replicates). Larvae were fed for 5 days and processed to make meal by drying and grinding; evaluating mortality, weight, size, proximal chemical composition, and apparent digestibility to determine the most viable substrate, analyzing effects and significance by multifactorial ANOVA and Kruskal-Wallis.FINDING: The results show Mortality (F = 917,81, p < 0,0001): T1 y T3 with 76,40 ± 2,86 (%) (F = 917,81, p < 0,0001), following T6 with 69,67 ± 4,55%, T7 with 24,00 ± 3,48%, T2 with 4,60 ± 1,92 %, T5 y T4, both with 4,20 ± 2,00 %. Weight (F = 825,62, p < 0,0001): T2 with 1,78 ± 0,22 gram outperformed the control T5 (1,76 ± 0,50 gram), T4 with 1,45 ± 0,06 g and T7 with 1,66 ± 0,07 gram. Size (F = 248,95, p < 0,0001): T5 with 16,03 ± 0,34 mm, T2 with 15,86 ± 0,22 mm, T4 with 14,72 ± 0,35 mm and finally, 14,51 ± 0,14 millimeter in T7. Proximal chemical analysis of crude protein and fat: T2 resulted in the following results 50,81 % and 21,88 %, T4 with 53,90% y 15,04%, T7 with 42,63 % and 32,03%, and T5 con 41,1 % and 19.55%, respectively. Digestibility: T5 with 20,39%, T2 with 12,66%, T4 with 10,61% and T7 with 5,97%. T2 raw beef viscera were determined to be the most viable substrate, followed by T4 cooked beef viscera and T7 cooked chicken viscera.CONCLUSIONS: Testing the effectiveness of cattle viscera as substrate, the experimental data presented may help design a process for an effective treatment method for slaughterhouse waste, which might benefit developing nations in managing their waste effectively, generating high protein meal, with the potential for a circular bioeconomy.